IMPLEMENTASI PERATURAN BUPATI MAHAKAM ULU NOMOR 25 TAHUN 2018 TENTANG PEDOMAN PENGENDALIAN GRATIFIKASI DI LINGKUNGAN KABUPATEN MAHAKAM ULU - Astuti, Renika; Surya, Iman; Paselle, Enos (Magister Administrasi Publik FISIP Universitas Mulawarman, 2022)
This study aims to analyze the implementation of gratification control policies, efforts in gratification control, as well as the supporting and inhibiting factors for the implementation of gratification control. This study uses a qualitative approach with a descriptive research model. The research data were obtained using interview and observation techniques and field studies. The data analysis model used is an interactive data analysis model. Testing the validity of the data is done by testing the reliability and validity of the data. The results showed that the gratification control policy had been implemented with the Gratification Control Unit Team as the implementer of the policy, but the results were not optimal, seen from the four aspects of policy implementation, namely communication, resources, disposition, and bureaucratic structure. Keywords: policy implementation, gratification control, communication, resources, disposition, bureaucratic structure